Sustaining the Environment in an Era of Small-Scale Mining in Ghana: Optimizing the Role of Institutions - Kokofu, Henry Kwabena; Kofi Sarfo-Adu, Gordon; Dadebo, Mark Aferdi; Nkrumah, Gladys; Galley, David Kwaku (International Journal of Global Sustainability, 2022)
The study aimed at assessing the common constraints that affect the enforcement of small-scale mining laws and regulations which have created a vacuum for illegal operators to infiltrate the space with the associated environmental and social cost implications. Underpinned by the institutional theory, the study analyzes from existing theoretical and empirical studies to assess why institutions and agencies on artisanal and small-scale mining find it difficult to clamp down on illegal gold extractive activities. Retrospective literature analysis was the main method employed by the study. A synthesis from the review suggests that key challenges revolve around poor allocation of resources, poor collaboration among multiple levels and sectors, protection rackets by powerful beings in society, connivance of some traditional authorities and members, poverty, green squeezing, and cumbersome nature of ASM licensing process in Ghana. The study contends on the one hand that laws, policies, and regulations are only as good as their enforcement; whilst on the other hand, enforcement is only as good as the laws and regulations formulated in the first place. The study discusses five policy suggestions that will go a long way to help enforcement of ASM policies and institutions in Ghana.